Acoustic Phonon Transmission and Thermal Conductance in a Three-Stub Quantum Waveguide (Journal of Atomic and Molecular Sciences, 2018)
Using the scattering matrix method, we investigate the acoustic phonon transmission and thermal conductance in a quantum waveguide with three stubs at low temperature. It is found that transmission coefficient shows periodic feature and the number of cutoff frequency bands increases with increasing of height h; and the thermal conductance exhibits oscillatory decaying behavior with increasing of the widths between any two stubs; In addition, thermal conductance is sensitive to the width and height of stubs; The results show that changing the geometric parameters of the stubs could provide an efficient way to control the thermal conductance of the proposed micro-structures artificially.
Keywords: T-shaped quantum waveguide; scattering matrix method; acoustic transmission coefficient; thermal conductance.